2007
DOI: 10.1108/14720700710827149
|View full text |Cite
|
Sign up to set email alerts
|

The top team: examining board composition and firm performance

Abstract: PurposeThis paper seeks to argue that boards can be playing a more proactive role in contributing to organizational effectiveness and that their composition requires greater research attention. By integrating the organizational behaviour literature on teams with the governance literature, the paper empirically examines the relationship between key board composition variables and firm performance.Design/methodology/approachAt this stage in the development of the approach, the focus is on a sub‐set of the elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 44 publications
5
59
1
Order By: Relevance
“…There are studies in samples of Eurozone countries that have found a positive relationship between size and profitability: Alves and Mendes (2004) in Portugal; Barroso et al (2009Barroso et al ( , 2010Fernández et al (1998);and Rodríguez Fernández et al (2013) in Spain. This has also been the case in international samples, or from countries outside Europe: Dalton et al (1999) and Larmou and Vafeas (2010) in international companies; Jackling and Johl (2009) and Raja and Kumar (2008) in India; Kiel and Nicholson (2003) in Australia; McIntyre et al (2007) in Canada; Reddy et al (2010) in New Zealand, and finally, Uadiale (2010) in Nigeria.…”
Section: Review Of the Literature: Theoretical Framework And Em-piricmentioning
confidence: 82%
“…There are studies in samples of Eurozone countries that have found a positive relationship between size and profitability: Alves and Mendes (2004) in Portugal; Barroso et al (2009Barroso et al ( , 2010Fernández et al (1998);and Rodríguez Fernández et al (2013) in Spain. This has also been the case in international samples, or from countries outside Europe: Dalton et al (1999) and Larmou and Vafeas (2010) in international companies; Jackling and Johl (2009) and Raja and Kumar (2008) in India; Kiel and Nicholson (2003) in Australia; McIntyre et al (2007) in Canada; Reddy et al (2010) in New Zealand, and finally, Uadiale (2010) in Nigeria.…”
Section: Review Of the Literature: Theoretical Framework And Em-piricmentioning
confidence: 82%
“…interdisciplinary teams) and that factors that lead to high performance in such teams also contribute to board effectiveness (e.g. McIntyre et al 2007;Payne et al 2009). …”
Section: Theoretical Backgroundmentioning
confidence: 98%
“…Board tenure is calculated as the average number of years that board members have served on a particular board (Golden & Zajac, 2001;Johnson, Hoskisson, & Hitt, 1993;Kaymak & Bektas, 2008;Kor & Sundaramurthy, 2009;McIntyre, Murphy, & Mitchell, 2007).…”
Section: Independent and Moderator Variablesmentioning
confidence: 99%